2005
DOI: 10.1007/s10201-005-0143-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salmon carcasses on egg production of a freshwater amphipod, Jesogammarus jesoensis: a field observation

Abstract: The effect of salmon carcasses on egg production of a freshwater amphipod, Jesogammarus jesoensis, was examined by comparing populations with and without a supply of carcasses in Naibetsu River in Hokkaido, northern Japan. The female body length in the population with carcasses became larger in the years when carcasses were abundant, being significantly larger than that in the population without carcasses. No evidence, however, was found that carcasses influenced the ratio of brooding females to mature females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…For example, when their habitat is rich in salmon carcasses, they tend to oviposit significantly more eggs (Kusano and Ito, 2005). Our research on the alien amphipod Crangonyx floridanus, however, showed no season-related fluctuations in batch or egg size.…”
Section: Egg Number Per Ovipositional Cycle Of Copulated Femalescontrasting
confidence: 54%
“…For example, when their habitat is rich in salmon carcasses, they tend to oviposit significantly more eggs (Kusano and Ito, 2005). Our research on the alien amphipod Crangonyx floridanus, however, showed no season-related fluctuations in batch or egg size.…”
Section: Egg Number Per Ovipositional Cycle Of Copulated Femalescontrasting
confidence: 54%
“…We observed amphipods, the dominant benthic invertebrate, on top of lake trout carcasses, suggesting potential for direct consumption. Amphipods consume many food resources, and high‐quality food resources such as carcass material can increase growth and fecundity (Cruz‐Rivera & Hay, 2000; Ito 2003; Kusano & Ito, 2005; MacNeil et al., 1997). Additionally, mobile taxa such as amphipods may immigrate to sites treated with carcass material and colonize the carcasses, which could cause increases in density and biomass evident at relatively short timescales (Chaloner et al., 2002).…”
Section: Discussionmentioning
confidence: 99%